Tinjauan Yuridis Pelaksanaan Perjanjian Sewa Menyewa Rumah Toko Di Wilayah Semarang Barat - Arif Rifqi Muslim; Achmad Busro (Magister Kenotariatan Universitas Diponegoro, 2022)
AbstractImplementation of lease agreements is often a problem in shophouse rentals. The focus of the problem in this study is How the Legal Review of the Implementation of the Rental Agreement for Shop Houses (ruko) in the City of Semarang, How the Legal Protection Forms the Rental-Renting Agreement for Shop Houses (ruko) The method used in this research is an empirical juridical approach, namely research that utilizes the laws of the environment in a real sense and examines how it works in the community which aims to understand what is done by research subjects and in a descriptive way in the form of words and language by utilizing various books. -scientific books. The results of this study indicate that the implementation of the lease agreement must go through the stages starting with the pre-agreement stage, the stage of the Agreement Preparation, the post-signing of the agreement. The form of legal protection The lease agreement is regulated in chapter VII of Book III of the Civil Code entitled